Financing coastal land use planning for sustainability - Asmawi, M. Zainora; Md. Din, Azrin; Mahamod, Lukman Hakim (2011)
The essential of planning and management of coastal areas has been widely accepted globally for nearly 40 years. However, the coastal policies, strategies and programmes are not extensively incorporated in the framework of Malaysian land use planning system. As such, this paper looks into the scenario of the planning and managing of coastal land uses in relation to the experience of Lembaga Urus Air Selangor. Coastal management requires other tools in delivering its wide array of development objectives and strategies to make it more sustainable. In this regards, the framework of development and planning process is seen as one of the available tools to plan and manage coastal areas. The analysis and findings demonstrate that the practice of Lembaga Urus Air Selangor relatively plans and manages their coastal land uses as in accordance with the physical land use planning system, encompassing the components of forward planning in their long term vision for their area. Though it is evident that the current practice works well, the system can be further improved taking into consideration other influential factors such as establishing database and financial aspect.